2023
DOI: 10.1002/jmv.28784
|View full text |Cite
|
Sign up to set email alerts
|

The causal links between gut microbiota and COVID‐19: A Mendelian randomization study

Abstract: Several studies have shown a possible correlation between gut microbiota and COVID-19. However, the cause-and-effect relationship between the two has not been investigated. We conducted a two-sample Mendelian randomization study (MR) study using publicly available GWAS data. Inverse variance weighted (IVW) analysis was the main MR analysis technique and was supplemented with other sensitivity analyses. Forty-two bacterial genera were associated with COVID-19 susceptibility, hospitalization, and severity in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Its potential to produce specific metabolites has not been fully studied. At present, class.Negativicutes is closely related to diseases such as COVID-19 ( Song et al., 2023 ), low birthweight infants ( Warner et al., 2016 ), and obesity ( Hu et al., 2022 ). In this study, it was found that there was a significant causal relationship between class.Negativicutes and insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Its potential to produce specific metabolites has not been fully studied. At present, class.Negativicutes is closely related to diseases such as COVID-19 ( Song et al., 2023 ), low birthweight infants ( Warner et al., 2016 ), and obesity ( Hu et al., 2022 ). In this study, it was found that there was a significant causal relationship between class.Negativicutes and insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…The IVs were chosen based on the following criteria: [ 1 ] The number of single nucleotide polymorphisms (SNPs) was too small when the candidate SNPs were filtered with the genome-wide significance threshold ( p < 5 × 10^-8) and thus might result in missing potential findings. In this study, locus-wide significance threshold ( p < 1 × 10 − 5) was used to select the potential SNPs associated with GM; [ 2 , 24 , 25 ] To avoid linkage disequilibrium, the SNPs were only retained after the clumping process (r 2 < 0.001 and window size = 10,000 kb); [ 3 ] Proxy SNPs with linkage disequilibrium R 2 > 0.8 were found to substitute the selected SNPs, which were not matched in GWAS of DN; [ 4 ] the SNPs were removed with a minor allele frequency (MAF) less than 0.01; [ 5 ] The strength of each SNP was measured by the F-statistics which was calculated by the following formula: , R 2 was the proportion of the variability of bacterial taxa explained by each SNP and N was the sample size [ 26 ]. For eliminating weak IVs, only those SNPs with F-statistics greater than 10 were kept; [ 6 , 27 ] To avoid the confounders related to SNPs affected DN, PhenoScanner V2, a database of human genotype-phenotype associations was used to recognize and weed out those SNPs linked to the confounding factors (hypertension, autoimmune disease, etc.…”
Section: Methodsmentioning
confidence: 99%
“…The estimates are expressed as odds ratios (ORs) with 95% confidence intervals (ci), which indicate the average change in outcomes resulting from each exposure. In this study, IVW method was used as the main analysis method, and other methods were used as auxiliary proof [ 21 ]. These results only provide evidence of a causal relationship between exposure and outcomes, with no other explanation.…”
Section: Methodsmentioning
confidence: 99%